2023
DOI: 10.30613/curesosc.1187599
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and Economic Growth Nexus: What has the Arab Spring Changed?

Abstract: Corruption is an everlasting phenomenon in the Middle East and North Africa (MENA). It is considered one of the fundamental reasons for the Arab incidents that started in Tunisia in 2011. Considering its devastating effects, this paper concentrates on the impacts of corruption at the macro level following the Arab uprisings. Notably, it investigates the impact of corruption on economic growth between 1996-2020. The paper utilizes panel estimators with country-fixed effect regressions given the results of the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
(46 reference statements)
0
0
0
Order By: Relevance
“…The mainstream literature focused on the relationship between political instability indicators and economic growth and, they came to the common consensus that the region's political instability hampered its economic growth. As well, policymakers' inability to plan ahead exacerbated the region's subpar performance in the short run and long run (Campos & Nugent,2002;KIRŞANLI, 2023;Tang & Abosedra, 2014) There is no doubt that the region's trajectory towards recovery requires more than 30 years in transition as per the analysis of regional experts (Carothers, 2002). More importantly, the region's complexity was aggravated through the presence of oil's vested interests and the rentier nature of some of its economy, which certainly took a toll on its governance indicators and border conflicts.…”
Section: Introductionmentioning
confidence: 99%
“…The mainstream literature focused on the relationship between political instability indicators and economic growth and, they came to the common consensus that the region's political instability hampered its economic growth. As well, policymakers' inability to plan ahead exacerbated the region's subpar performance in the short run and long run (Campos & Nugent,2002;KIRŞANLI, 2023;Tang & Abosedra, 2014) There is no doubt that the region's trajectory towards recovery requires more than 30 years in transition as per the analysis of regional experts (Carothers, 2002). More importantly, the region's complexity was aggravated through the presence of oil's vested interests and the rentier nature of some of its economy, which certainly took a toll on its governance indicators and border conflicts.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of our paper have important implications for various United Nations' Sustainable Development Goals (SDG) due to the interrelationships between corruption, income inequality, and economic growth. This is due to the fact not only corruption has been shown to affect economic growth negatively (d'Agostino et al, 2016; Kırşanlı, 2023; Mauro, 1995), but income inequality has also been shown to be significantly associated with economic growth (Banerjee & Duflo, 2003). Therefore, corruption cannot only impact growth directly but will also have indirect effects through a change in income inequality.…”
Section: Introductionmentioning
confidence: 99%